Desarrollo del portal web de la Universidad Nacional de Loja, aplicando técnicas de web semántica en el gestor de contenidos DRUPAL. - Álvarez Pacheco, Máximo Andrés (2016)
In order to carry out the thesis project, three steps were performed: problem identification, objectives, state of the art combined with methodologies to create Web Portals, giving to this project the steps to solve the problem established The study of success cases was performed in order to identify in which aspects the Semantic Web contributes to the content of Web portals in general, which institutions of Higher Education have criteria for the Semantic Web. Also, it was determined, based on a study of systems content management, that the CMS (Content Managed System) Drupal is one of the best alternatives (OpenSource) for web content management taking as sample for this study three content management systems (Drupal, Wordpress and Joomla). We proceeded with implementation of phases which have the Methodology for creating Web sites starting from an analysis of project objectives, continuing with the process of planning and construction. Process described from the server configuration to integration techniques of the Semantic Web (RDF - Resource Description Framework) in the CMS Drupal, specifically the use of technologies that the architecture of the Semantic web display in the first three layers (Architecture expounded by Tim Berners-Lee), continuing with the phase of Testing and Test, on the proposed solution, for a better understanding of the terms Verification and Testing. As a final phase, a diffusion of the posed solution was made to the university authorities and its community.